Production errors and interlanguage development patterns of L1 Malay ESL learners in the acquisition of the English passive - Mahdun, Mahanum; Chan, Mei Yuit; Yap, Ngee Thai; Mohd Kasim, Zalina; Wong, Bee Eng (UNIMAS Publisher, 2022)
Studies have shown that Malay ESL learners face difficulties in acquiring the English passive, but not much is known about their acquisition patterns as they advance in their proficiency in English. This study investigated the interlanguage development patterns of L1 Malay learners by examining the production errors of learners at varying English proficiency levels. Students from tertiary institutions in Malaysia completed tasks designed to elicit production of the English passive. The results indicated that overall, the main errors committed by the learners were related to the be-auxiliary and the past participle verb form, which are non-existent in their L1. Certain types of errors diminished at higher English proficiency levels, whilst certain others persisted in high proficiency learners. These results point to underlying differences in sources of errors where some types of errors are more resistant to change, while others may be resolved as the interlanguage system develops to approximate the target language. Differential pedagogical interventions may be indicated for learners at different stages of L2 acquisition.